Peningkatan Hasil Belajar Servis Atas Menggunakan Net Gawang Futsal Pada Siswa SMP Kelas VII: Penelitian - Farid Akbar Ash Shidiqie; Septyaning Lusianti; Muhammad Rofi’Ussya’en; Zahro Ruhanah; Sugaloh Indriamawati (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Basically, teachers are required to have varied creativity and innovation to solve the problem of decreasing enthusiasm for learning in students. In this study, the researcher focused more on the basic technique of upper service in volleyball games for class VII students of SMPN 7 Kota Kediri using a futsal goal net. To find out whether students are interested in the method, each meeting the teacher makes an assessment, the value obtained can determine whether the alternative can be said to be effective in applying to learning or not. In this study, the type of research is classroom action research, or commonly called (PTK). Which obtained the pre-cycle results obtained an average value of 66.1, the first cycle obtained an average value of 80.2, the second cycle obtained an average value of 85.2, the number of students who completed was 27. So modifying the net used in volleyball games using futsal goals can be said to be effective for use during learning.